2020
DOI: 10.28991/cej-2020-03091583
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Self-compacting High Performance Concrete Containing Calcined Kaolin Clay and Nano Lime

Abstract: The aim of this research is to investigate the effect of pozzolanic materials and nano particles on improve the strength characteristic by the properties of a self-compacting high-performance concrete that includes calcined clay with nano lime. In this study, two blends systems are worked on, they are the binary and the ternary systems. For binary mixtures, test samples were prepared from 5% CC, 10% CC, 15% CC and 3% NL by partial replacement of the cement weight. While ternary mixtures, samples were prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In Figure 17, ternary mixtures containing 30%CKC 10%WMP and 30%CKC 10%LP perform better than binary blends of 30%CKC and the control blend of 100%OPC at 7 and 28 days. Generally, the splitting tensile strength for all types of binary and ternary blends SCC mixes cured of 3 to 90 days was in the range of 7.4-7.92% of their respective compressive strengths, which is less than the outcomes of concretes of average strength, which range from about 8% to 10% [24].…”
Section: Splitting Tensile Strengthmentioning
confidence: 81%
See 1 more Smart Citation
“…In Figure 17, ternary mixtures containing 30%CKC 10%WMP and 30%CKC 10%LP perform better than binary blends of 30%CKC and the control blend of 100%OPC at 7 and 28 days. Generally, the splitting tensile strength for all types of binary and ternary blends SCC mixes cured of 3 to 90 days was in the range of 7.4-7.92% of their respective compressive strengths, which is less than the outcomes of concretes of average strength, which range from about 8% to 10% [24].…”
Section: Splitting Tensile Strengthmentioning
confidence: 81%
“…The percentage and quality of calcined kaolin clay (CKC), waste marble powder (WMP), and limestone powder (LP), as well as their combined effects, are important factors that lessens passing ability similarly to how it decreases filling ability. Some studies reported similar outcomes [21][22][23][24]. The issue might be attributed to the long, hexagonal plates of the calcined kaolin clay, which hinder the smooth flow of the freshly mixed material and increase friction among the components.…”
Section: Fresh Experimental Resultsmentioning
confidence: 97%
“…These effects of nano lime on SCGPC's fresh characteristics were similar to those found by Ge (43) and Kadhum and Owaid. (23) They found that adding nano-lime to SCC leads to decreased slump flow diameter, L-box height ratio, and increased V-funnel flow times (i.e., increased mixture viscosity). The following paragraphs covered the impact of nano lime on each fresh property test.…”
Section: Results and Discussion Fresh Propertiesmentioning
confidence: 99%
“…Nano-lime (NL) is cheaper because its abundant supply in limestone and marble, making it suitable for cementitious composites as a filler and nucleation agent. (23,24) However, new research by Assadi et al (17) assessed the inclusion of Calcium Carbonate nanoparticles (NC) in geopolymeric paste based on fly ash up to a 3 % content. While increasing the amount of NC to 2 % enhanced the mechanical characteristics of geopolymer composites, increasing it to 3 % decreased GPC mechanical performance.…”
Section: Introductionmentioning
confidence: 99%
“…Pozzolan material itself has long been known in Indonesia as a building material that is mixed lime outages [7]. Recently, pozzolan materials even studied to be implemented as waterproof material for DAM soil [8]. It is even possible to use alkali-activated natural pozzolans to prepare environmentally friendly geopolymer cement leading to the concept of sustainable development [9].…”
Section: Pozzolan Materialsmentioning
confidence: 99%